New Media and Digital Pedagogy: Enhancing the Twenty-First-Century Classroom - Strawser, Michael G. (Lexington Books, 2017)
New Media and Digital Pedagogy: Enhancing the Twenty-First-Century Classroom addresses the influence of new media on instruction, higher education, and pedagogy. The contributors specifically examine the practical and theoretical implications of new media and the influence of new media on education. This book emphasizes the changing landscape of education and technology and creates a foundational lens and framework for thinking through and navigating higher education in a digital and new media driven context.